2006
DOI: 10.1177/0272431606291939
|View full text |Cite
|
Sign up to set email alerts
|

Family Environment, Effortful Control, and Adjustment Among European American and Latino Early Adolescents

Abstract: The present study examined the independent and interactive relations of effortful control and two family environment variables (parent-adolescent conflict and negative family relations) on the subsequent conduct problems and depressive symptoms of 459 European American and Latino adolescents between the ages of 10 and 14. Hierarchical regression analyses showed that even after baseline levels of conduct problems were taken into account, lower levels of effortful control and poorer family relations were uniquel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 55 publications
7
44
0
Order By: Relevance
“…Cognitive problem-solving, coping effectiveness, scholastic achievement, gender identification, and effortful control were not protective for African American and Hispanic adolescents (Gerard and Buehler 2004;Loukas and Roalson 2006;McCoy and Major 2003;Tolan et al 2013). In fact, cognitive problem-solving and scholastic achievement increased the risk of depressed mood among African American adolescents in one study (Gerard and Buehler 2004).…”
Section: Not Protectivementioning
confidence: 83%
“…Cognitive problem-solving, coping effectiveness, scholastic achievement, gender identification, and effortful control were not protective for African American and Hispanic adolescents (Gerard and Buehler 2004;Loukas and Roalson 2006;McCoy and Major 2003;Tolan et al 2013). In fact, cognitive problem-solving and scholastic achievement increased the risk of depressed mood among African American adolescents in one study (Gerard and Buehler 2004).…”
Section: Not Protectivementioning
confidence: 83%
“…Results for self-regulatory measures of temperament were consistent, although based on only a few studies. Two studies examined inhibitory control and did not find significant interactions (Olson et al, 2000;Rioux et al, 2016) and three studies examined effortful control, finding significant interactions (Bakker et al, 2011;Loukas & Roalson, 2006;Sentse et al, 2011). One additional cross-sectional study examined duration of orienting and attentional focus and found significant interactions (Windle, 1992).…”
Section: Interactions Between Temperament and The Family Environmentmentioning
confidence: 98%
“…Effect sizes were small when the interaction involved coercive parenting and mother-infant affectionate contact, but it was of medium magnitude when the interaction involved parental monitoring. Conversely, three studies examined effortful control and found significant interactions that supported the diathesis-stress model (Bakker et al, 2011;Loukas & Roalson, 2006;Sentse et al, 2011), all with small effect sizes and large sample sizes. These three studies used data exclusively in adolescence and two of them used data from the same sample (Bakker et al, 2011;Sentse et al, 2011).…”
Section: Self-regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is not a singular definition for school climate, most researchers agree that a positive school climate exists when all students feel comfortable, wanted, valued, accepted, and secure in an environment where they can interact with caring people they trust (Loukas & Robinson, 2004). Collectively and individually, a positive school climate can have a major impact on the success of all students in the school (Loukas & Roalson, 2006). Moreover, a positive school climate can have a major impact on teachers and their job satisfaction and efficacy (Taylor & Tashakkori, 1995).…”
Section: Introductionmentioning
confidence: 99%